Basic Survival Needs and Access to Medicines - Coming to Grips with TRIPS: Conversion plus Calculation - Van Puymbroeck, R. V. (2012)
"Access to medicines" is a broad concept. After a review of three authoritative frameworks that help to identify its constitutive components, this essay summarizes the actual situation on the ground in low- and middle-income countries on the basis of recent empirical work. An analysis of survey data from 36 countries concluded that developing countries should promote generic medicines as a key policy option for improving access to medicines. Taking an international perspective to that recommendation, this essay reviews the World Trade Organization's Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS) and, particularly, how this agreement has been applied in practice. As shown by the experience of Thailand, Brazil, and the Philippines, in order to deal effectively with international pressures for an excessive application of the TRIPS Agreement, some sort of conversion experience appears to be required, which then leads to a switch from a private enterprise, supply-driven approach to a public health vision that insists on universal and affordable access. But moral conviction is not sufficient. In order to muster and sustain the political will to face down international forces, civil society and government offices must be able and ready to show the costs and other adverse consequences of the TRIPS-based model for medicines. This calculation needs to reach beyond the health sector and calls for new alliances, nationally as well as internationally.